Kontribusi Ustadz, Ustadzah, dan Pengurus Pondok Pesantren Terhadap Pembentukan Karakter Santri (Studi Kasus Pondok Pesantren Fathul Ulum) - Silfi Alfi Ahmida; Tarida, Lesna; Supadmi; Agus Suprayogi (BAMALA Institute, 2025)
Character education is very important in shaping the morals and personalities of students in Islamic boarding schools. This study analyzes the role of administrators and ustadz at the Fathul Ulum Islamic Boarding School in Jombang in shaping the character of students through an exemplary approach, teaching Islamic values, and habituating daily discipline. Administrators and ustadz function as primary guides, not only in teaching yellow books and worship, but also in instilling noble morals, discipline, and responsibility through social interaction and motivation. Amid the influence of globalization, their role is crucial in creating honest, disciplined, and responsible students as the nation's successors. The approach in this study is descriptive qualitative research, key informants in this study are ustadz and ustadzah, while students are used as additional informants. Data collection techniques in this study use observation, interviews and documentation, data analysis techniques with data reduction, data presentation and drawing conclusions. The results of this study can be stated that the role of administrators and ustadz at the Fathul Ulum Islamic Boarding School is very crucial in shaping the character of students. Through teaching methods based on Islamic values, administrators and ustadz (Islamic teachers) not only teach religious knowledge but also act as role models, providing direct guidance in the students' daily lives. They play an active role in instilling discipline, responsibility, and noble morals by practicing these values ​​through exemplary behavior in worship and social interactions. Furthermore, administrators and ustadz also provide motivation and guidance to students so they can live a balanced life between religious knowledge and general knowledge.